Resenha do volume "Studies in Southern History" - Goldman, Frank (Revista de História, 2015)
Studies in Southern History. Chapel Hill. The University of North Carolina Press, 1957. Vol. 39 do James Sprunt Studies in History and Political Science, editado por Fletcher M. Green diretor, William Whathey Pierson, J. Carlyle Sitterson e James E. King. 168 págs.